A TiSiNiYN coating for enhancing high temperature wear resistance

By introducing Ni and Y elements into the TiSiN coating, the TiSiNiYN coating was prepared, and the problem of peeling off the existing TiSiN coating at high temperatures was solved, achieving high-temperature wear resistance and better The bonding force extends the service life of the tool.

CN118086841BActive Publication Date: 2025-02-07NASHI NEW MATERIALS CO LTD HANGZHOU BRANCH +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410226610.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-03-29
Filing Date
2024-02-29
Publication Date
2025-02-07
Estimated Expiration
2044-02-29

AI Technical Summary

Technical Problem

The existing TiSiN coatings are prone to peel off at high temperatures and cannot meet the high-temperature oxidation resistance requirements of modern high-speed cutting and dry cutting technologies.

Method used

The TiSiNiYN coating is used to improve the binding force and wear resistance of the coating by arc ion coating with a TiSiNiY alloy target under a nitrogen-containing atmosphere.

Benefits of technology

The high-temperature wear resistance of TiSiNiYN coating is achieved, the friction coefficient is reduced, the bonding force between the coating and the substrate is enhanced, and the service life of the tool is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118086841B_ABST
    Figure CN118086841B_ABST
Patent Text Reader

Abstract

The present invention discloses a TiSiNiYN coating for enhancing high-temperature wear resistance, and relates to the technical field of surface coatings. The TiSiNiYN coating is arc ion plated with a TiSiNiY alloy target to deposit a TiSiNiYN layer on a substrate, and the obtained high-temperature wear-resistant TiSiNiYN coating has a lower friction coefficient, good bonding between the coating and the substrate, and has an effect of improving the service life of the tool; in addition, the present invention also provides a substrate detergent, and the substrate treated with the detergent is used for the preparation of the coating, so that the prepared TiSiNiYN coating has a better bonding between the substrate and the substrate, and has an effect of improving the service life of the tool.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface coatings, and in particular relates to a TiSiNiYN coating for enhancing high-temperature wear resistance. Background Art

[0002] With the progress of society and the development of science and technology, the requirements for material surface performance are getting higher and higher. High hardness, wear resistance, corrosion resistance, elastic modulus and other indicators are important indicators to measure the performance of today's cutting tools. In order to meet the increasingly high engineering needs, coating a layer of hard coating on the surface of the material is an economical and practical way to improve the surface performance of the material. As an important branch of mechanical functional membranes, hard coatings are widely used in mechanical processing tools.

[0003] Initially, TiN coatings have attracted widespread attention due to their outstanding properties such as high hardness, wear resistance, corrosion resistance and good decorativeness. Later, in order to further improve the hardness and high-temperature oxidation resistance of TiN coatings, people prepared TiSiN nanocomposite structure coatings by adding silicon elements, and their performance has been greatly improved. However, as the current cutting technology gradually develops towards high-speed cutting and dry cutting, such tool coatings have gradually failed to meet the requirements of modern cutting technology, so there is an urgent need to develop new protective coating materials. With the development of nanoscience and technology, further research on nanocomposite coatings has become an important development direction for hard coating materials. The so-called nanocomposite film coating is a typical superhard coating reinforced with nanostructures. The coating is a three-dimensional network structure formed by the interface phase wrapping the matrix phase. Its hardening mechanism is related to the composite structure of the interface phase wrapping the nanocrystals.

[0004] In recent years, TiSiN coatings have been widely used as protective coatings for knives and tools. Because TiSiN introduces Si elements into TiN coatings, it can form Si3N4 amorphous structures to wrap TiN grains, refine the grains, and increase the hardness of the coating. At the same time, Si elements can form dense oxide films at high temperatures, which greatly improves the high-temperature oxidation resistance of the coating. With the further development of modern processing, the processing line speed is getting higher and higher, and the high-temperature resistance of the coating is required to be further improved. The amount of Si elements added in the TiSiN coating needs to be further increased, but the addition of Si elements also greatly increases the compressive stress of the coating, making the coating's bonding strength worse. The greater the amount of Si elements added, the greater the stress of the coating, which makes the coating extremely easy to peel off. Therefore, a single TiSiN coating can no longer meet the demand. Summary of the invention

[0005] The object of the present invention is to provide a TiSiNiYN coating for enhancing high temperature wear resistance, wherein the TiSiNiYN coating has a lower friction coefficient, good bonding force between the coating and a substrate, and can improve the service life of a tool.

[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:

[0007] A coating for enhancing high temperature wear resistance comprises a TiSiNiYN coating plated on a substrate surface.

[0008] The present invention also discloses a method for preparing a TiSiNiYN coating for enhancing high-temperature wear resistance, comprising: arc ion plating a TiSiNiY alloy target in a nitrogen-containing atmosphere to deposit a TiSiNiYN layer on a substrate to obtain a TiSiNiYN coating for enhancing high-temperature wear resistance.

[0009] Specifically, the method for preparing the TiSiNiYN coating for enhancing high temperature wear resistance comprises the following steps:

[0010] Nitrogen is introduced, the gas pressure is controlled at 5-7Pa, the arc target power supply of the TiSiNiY alloy target is turned on to perform arc ion plating on the substrate surface, the target current is 100-200A, the bias voltage of the substrate is -100 to 100V, and the deposition time is 1-6h to obtain a coating for enhancing high temperature wear resistance, namely a TiSiNiYN coating.

[0011] According to an embodiment of the present invention, in the above TiSiNiY alloy target, by percentage, the content of Si is 8-15wt%, the content of Ni is 5-10wt%, the content of Y is 2-5wt%, and Ti is the balance.

[0012] In order to further enhance the performance of the TiSiNiYN coating, the present invention also performs deep cleaning on the substrate.

[0013] The substrate cleaning method comprises: polishing the substrate, spraying a detergent on the surface of the substrate, peeling off after drying to form a film, washing with ultrapure water for 3-5 times, immersing the substrate in ultrapure water (the mass volume ratio of the substrate to the ultrapure water is 1g:25-30mL), ultrasonically treating for 25-35min, immersing the substrate in ethanol (the mass volume ratio of the substrate to the ethanol is 1g:25-30mL), ultrasonically treating for 25-35min, and drying for use.

[0014] According to an embodiment of the present invention, the amount of the detergent is 0.1-0.15 mL / cm 2 .

[0015] According to an embodiment of the present invention, the detergent comprises: polyvinyl butyral, ethyl cellulose, and 2-nitrocinnamic acid.

[0016] The invention provides a detergent, which contains biodegradable ethyl cellulose, reduces post-processing work and avoids secondary pollution; in addition, it also contains polyvinyl butyral and 2-nitrocinnamic acid, which intersperse, overlap and entangle with the ethyl cellulose molecular chains, and fix pollutants in the film as the solvent evaporates and solidifies to form a film, and the pollutants are removed after peeling; and the functional groups such as nitro and carboxyl in the 2-nitrocinnamic acid can enhance the complexing ability with the pollutants, and the detergent removes the pollutants on the surface of the substrate in a dissolving, encapsulating and complexing manner, so that the bonding force between the TiSiNiYN coating and the substrate is enhanced.

[0017] The invention also discloses a method for preparing a detergent, which comprises: adding polyvinyl butyral into a mixed solvent of ethanol and ethyl acetate, and after dissolving, adding ethyl cellulose and 2-nitrocinnamic acid, stirring and dissolving, and then setting aside.

[0018] According to an embodiment of the present invention, the volume ratio of the ethanol to ethyl acetate is 1:1-1.5; the mass volume ratio of polyvinyl butyral to the mixed solvent is 1g:15-18mL; the mass ratio of polyvinyl butyral to ethyl cellulose is 1:0.45-0.65.

[0019] According to an embodiment of the present invention, the concentration of the 2-nitrocinnamic acid in the detergent is 6-8 g / L.

[0020] The invention also discloses the use of the detergent obtained by the preparation method in preparing a high-temperature wear-resistant coating.

[0021] Since the coating prepared by arc ion plating is prone to produce "droplets" during arc ion plating, which increases the roughness of the surface of the prepared coating, the present invention further performs a pore sealing treatment on the prepared TiSiNiYN coating. The pore sealing treatment can further reduce the friction coefficient of the coating, improve its wear resistance, and improve the service life of the tool.

[0022] The present invention also discloses a sealing method, comprising: applying a sealing agent to the prepared TiSiNiYN coating by a brushing process, drying in the shade at room temperature, heating to 102-110°C and keeping it for 3-4.5h, with a heating rate of 0.8-1.5°C / min, and after the insulation, heating to 600-650°C at a heating rate of 1.8-3°C / min and sintering for 25-40min to obtain a sealing layer.

[0023] According to an embodiment of the present invention, the above-mentioned brush coating thickness is 45-55 mg / cm 2 .

[0024] According to an embodiment of the present invention, the sealing agent comprises sodium silicate nonahydrate, mica powder, modified quartz, silica sol, chromium trioxide and nickel oxide.

[0025] The invention also discloses a method for preparing a sealing agent, comprising: adding silica sol to sodium silicate nonahydrate, stirring and mixing at 88-93° C. until it becomes clear, cooling to room temperature, adding mica powder, modified quartz, chromium trioxide and nickel oxide, mixing evenly, and obtaining the sealing agent.

[0026] According to an embodiment of the present invention, the mass ratio of the above-mentioned sodium silicate nonahydrate to silica sol is: 1:1.2-1.6; the mass ratio of sodium silicate nonahydrate to mica powder is: 1:0.4-0.6; the mass ratio of sodium silicate nonahydrate to modified quartz is: 1:0.5-0.8; the mass ratio of sodium silicate nonahydrate to chromium trioxide is: 1:0.3-0.42; the mass ratio of sodium silicate nonahydrate to nickel oxide is: 1:0.15-0.2.

[0027] The invention also discloses a method for preparing modified quartz, comprising: using 3-chloropropyltriethoxysilane to bond to the quartz surface in a chemical bonding manner, and then performing a substitution reaction with 2-amino-5-cyanopyridine to obtain the modified quartz.

[0028] The invention provides a preparation method of modified quartz. The modified quartz is prepared by chemically bonding hydroxyl groups on the surface of quartz with 3-chloropropyltriethoxysilane and then reacting with 2-amino-5-cyanopyridine. The modified quartz is then used in a sealing treatment process of a TiSiNiYN coating, so that the TiSiNiYN coating has a lower friction coefficient and has an effect of improving the service life of a tool.

[0029] Specifically, the preparation method of the modified quartz comprises the following steps:

[0030] The quartz is dried at 145-153°C for 50-80 min, then added to a nitric acid solution with a concentration of 0.8-1.3 mol / L (the mass volume ratio of quartz to nitric acid solution is: 1 g: 10-20 mL), soaked at room temperature for 20-30 h, filtered, washed with water, dried, then added to ethanol (the mass volume ratio of quartz to ethanol is: 1 g: 10-20 mL) and soaked for 25-35 min, filtered, washed with water and dried, then added to a 3-chloropropyltriethoxysilane solution, reacted at 70-85°C for 4.5-6 h, filtered, washed with ethanol 3-5 times, washed with ether 3-5 times, dried, then added to an ethanol solution of 2-amino-5-cyanopyridine, heated under reflux for 6-10 h, filtered, washed with ethanol 3-5 times, washed with ether 3-5 times, washed with deionized water 3-5 times, and dried to obtain modified quartz.

[0031] According to an embodiment of the present invention, the mass ratio of the quartz to 3-chloropropyltriethoxysilane is 1:0.15-0.3; the mass ratio of the quartz to 2-amino-5-cyanopyridine is 1:0.3-0.5.

[0032] According to an embodiment of the present invention, the solvent of the above-mentioned 3-chloropropyltriethoxysilane solution is a mixture of ethanol and water, and the mass volume ratio of the 3-chloropropyltriethoxysilane solution to the mixture is: 1g:2.5-4mL; the volume ratio of ethanol to water is: 1:0.4-0.7.

[0033] According to an embodiment of the present invention, the mass volume ratio of 2-amino-5-cyanopyridine to ethanol in the above-mentioned 2-amino-5-cyanopyridine ethanol solution is: 1g:7-13mL.

[0034] The invention also discloses the use of the modified quartz obtained by the preparation method in preparing a high-temperature wear-resistant coating.

[0035] The beneficial effects of the present invention include:

[0036] The present invention obtains a TiSiNiYN coating for enhancing high-temperature wear resistance. The TiSiNiYN coating is arc ion plated with a TiSiNiY alloy target to deposit a TiSiNiYN layer on a substrate. The obtained high-temperature wear-resistant TiSiNiYN coating has a low friction coefficient, good bonding between the coating and the substrate, and has an effect of improving the service life of the tool; in addition, the present invention also provides a substrate decontaminant, and the substrate obtained after using the decontaminant is used to prepare the coating, so that the prepared TiSiNiYN coating has a better bonding force with the substrate. The present invention also provides a preparation method of modified quartz, using 2-amino-5-cyanopyridine to modify quartz; then the modified quartz is used in the sealing process of the TiSiNiYN coating, so that the TiSiNiYN coating has a low friction coefficient, and has an effect of improving the service life of the tool.

[0037] Therefore, the present invention provides a TiSiNiYN coating for enhancing high-temperature wear resistance. The TiSiNiYN coating has a lower friction coefficient, good bonding strength between the coating and the substrate, and improves the service life of the tool. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 These are the infrared spectra test results of the modified quartz and quartz prepared in Example 6. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solution and advantages of the present invention more clear, the technical solution of the present invention is further described in detail below in conjunction with specific implementation methods:

[0040] The TiSiNiY alloy target used in the embodiment of the present invention was purchased from Baoji Hongyusheng Metal Processing Co., Ltd.

[0041] Embodiment 1:

[0042] A method for preparing a TiSiNiYN coating for enhancing high temperature wear resistance comprises the following steps:

[0043] Nitrogen gas was introduced with the gas pressure controlled at 5 Pa, and the arc target power supply of the TiSiNiY alloy target was turned on to perform arc ion plating on the substrate surface. The target current was 100 A, the bias voltage of the substrate was 50 V, and the deposition time was 2 h to obtain a TiSiNiYN coating for enhancing high-temperature wear resistance; wherein, in the TiSiNiY alloy target, by percentage, the content of Si was 15wt%, the content of Ni was 10wt%, the content of Y was 5wt%, and the content of Ti was 70wt%.

[0044] Embodiment 2:

[0045] The difference between a method for preparing a TiSiNiYN coating for enhancing high-temperature wear resistance and Example 1 is that a sealing treatment is performed.

[0046] A sealing method, comprising: applying a sealing agent to a TiSiNiYN coating by brushing, drying in the shade at room temperature, heating to 102°C for 4.5 hours, heating at a rate of 0.8°C / min, and then heating to 650°C at a rate of 1.8°C / min for 25 minutes to obtain a sealing layer. The thickness of the coating is 45 mg / cm 2 .

[0047] The preparation method of the sealing agent comprises: adding silica sol to sodium silicate nonahydrate, stirring and mixing at 88°C until it becomes clear, cooling to room temperature, adding mica powder, quartz, chromium trioxide and nickel oxide, mixing evenly, and obtaining the sealing agent. The mass ratio of sodium silicate nonahydrate to silica sol is 1:1.2; the mass ratio of sodium silicate nonahydrate to mica powder is 1:0.4; the mass ratio of sodium silicate nonahydrate to quartz is 1:0.5; the mass ratio of sodium silicate nonahydrate to chromium trioxide is 1:0.3; and the mass ratio of sodium silicate nonahydrate to nickel oxide is 1:0.15.

[0048] Embodiment 3:

[0049] The difference between a method for preparing a TiSiNiYN coating for enhancing high-temperature wear resistance and Example 2 is that the preparation method of the sealing agent is different.

[0050] The preparation method of modified quartz comprises the following steps:

[0051] The quartz was dried at 145°C for 80 min, then added to a 0.8 mol / L nitric acid solution (the mass volume ratio of quartz to nitric acid solution is: 1 g: 10 mL), soaked at room temperature for 20 h, filtered, washed with water, dried, then added to ethanol (the mass volume ratio of quartz to ethanol is: 1 g: 10 mL) and soaked for 25 min, filtered, washed with water and dried, then added to an ethanol solution of 2-amino-5-cyanopyridine, heated under reflux for 6 h, filtered, washed with ethanol 3 times, washed with ether 3 times, washed with deionized water 3 times, and dried to obtain modified quartz. Among them, the mass ratio of quartz to 3-chloropropyltriethoxysilane is 1:0.15; the mass ratio of quartz to 2-amino-5-cyanopyridine is 1:0.3; the solvent of the 3-chloropropyltriethoxysilane solution is a mixture of ethanol and water, the mass volume ratio of the 3-chloropropyltriethoxysilane solution to the mixture is 1 g:2.5 mL, and the volume ratio of ethanol to water is 1:0.4; the mass volume ratio of 2-amino-5-cyanopyridine to ethanol in the ethanol solution of 2-amino-5-cyanopyridine is 1 g:7 mL.

[0052] Embodiment 4:

[0053] The difference between a method for preparing a TiSiNiYN coating for enhancing high-temperature wear resistance and Example 2 is that the substrate is cleaned.

[0054] The substrate cleaning method comprises: after polishing the substrate, spraying a detergent on the surface of the substrate, peeling it off after drying to form a film, washing it with ultrapure water for 3 times, immersing the substrate in ultrapure water (the mass volume ratio of the substrate to the ultrapure water is 1g:25mL), ultrasonically treating it for 25min, immersing it in ethanol (the mass volume ratio of the substrate to the ethanol is 1g:25mL), ultrasonically treating it for 25min, and drying it for standby use; wherein the amount of the detergent is 0.1mL / cm 2 .

[0055] The preparation method of a detergent comprises: adding polyvinyl butyral to a mixed solvent of ethanol and ethyl acetate, and after dissolving, adding ethyl cellulose and 2-nitrocinnamic acid, stirring and dissolving for standby use; wherein the volume ratio of ethanol to ethyl acetate is 1:1; the mass volume ratio of polyvinyl butyral to the mixed solvent is 1g:15mL; the mass ratio of polyvinyl butyral to ethyl cellulose is 1:0.45; and the concentration of 2-nitrocinnamic acid in the detergent is 6g / L.

[0056] Embodiment 5:

[0057] The difference between a method for preparing a TiSiNiYN coating for enhancing high temperature wear resistance and Example 4 is that the preparation method of the detergent is different.

[0058] The difference between the preparation method of the detergent and that of Example 4 is that 2-nitrocinnamic acid is not added.

[0059] Embodiment 6:

[0060] The difference between a method for preparing a TiSiNiYN coating for enhancing high-temperature wear resistance and Example 4 is that the preparation method of the sealing agent is different.

[0061] The difference between the preparation method of the sealing agent and that of Example 4 is that modified quartz is used instead of quartz.

[0062] The preparation method of modified quartz comprises the following steps:

[0063] The quartz was dried at 145°C for 80 min, then added to a 0.8 mol / L nitric acid solution (the mass volume ratio of quartz to nitric acid solution is: 1 g: 10 mL), soaked at room temperature for 20 h, filtered, washed with water, dried, then added to ethanol (the mass volume ratio of quartz to ethanol is: 1 g: 10 mL) and soaked for 25 min, filtered, washed with water and dried, then added to an ethanol solution of 2-amino-5-cyanopyridine, heated under reflux for 6 h, filtered, washed with ethanol 3 times, washed with ether 3 times, washed with deionized water 3 times, and dried to obtain modified quartz. Among them, the mass ratio of quartz to 3-chloropropyltriethoxysilane is 1:0.15; the mass ratio of quartz to 2-amino-5-cyanopyridine is 1:0.3; the solvent of the 3-chloropropyltriethoxysilane solution is a mixture of ethanol and water, the mass volume ratio of the 3-chloropropyltriethoxysilane solution to the mixture is 1 g:2.5 mL, and the volume ratio of ethanol to water is 1:0.4; the mass volume ratio of 2-amino-5-cyanopyridine to ethanol in the ethanol solution of 2-amino-5-cyanopyridine is 1 g:7 mL.

[0064] Embodiment 7:

[0065] The difference between a method for preparing a TiSiNiYN coating for enhancing high-temperature wear resistance and Example 5 is that the preparation method of the sealing agent is different.

[0066] The difference between the preparation method of the sealing agent and that of Example 5 is that modified quartz is used instead of quartz.

[0067] The preparation method of modified quartz is the same as that of Example 6.

[0068] Test example:

[0069] 1. Infrared spectrum test

[0070] The samples were analyzed by infrared spectroscopy using a BRUKER Vector33 Fourier transform infrared spectrometer from BRUKER, Germany, with a scanning range of 400-4000 cm -1 .

[0071] The modified quartz and quartz prepared in Example 6 were tested as above, and the results are as follows: Figure 1 As shown. Figure 1 It can be seen that compared with the infrared spectrum of quartz, the infrared spectrum of modified quartz is at 1664cm -1 There is an infrared characteristic absorption peak of the pyridine ring at 2252 cm -1 There is an infrared characteristic absorption peak of C≡N bond at the position, indicating that 2-amino-5-cyanopyridine participates in the formation reaction of modified quartz.

[0072] 2. Elemental composition test of coating

[0073] The element distribution in the coating samples was analyzed using an energy spectrum analyzer.

[0074] Table 1 Test results of element content

[0075]

[0076] The above test was performed on the TiSiNiYN coating prepared in Example 1. The test results of the element content of the TiSiNiYN coating are shown in Table 1.

[0077] 3. Friction coefficient test

[0078] Veeco NT9300 white light interferometer was used to measure the friction coefficient of the coating.

[0079] Table 2 Test results of friction coefficient

[0080]

[0081] The above test was performed on the TiSiNiYN coatings prepared in Examples 1 to 3, and the results are shown in Table 2. As can be seen from Table 2, compared with Example 2, Example 3 has a significantly lower friction coefficient, indicating that after 2-amino-5-cyano-modified quartz is used in the pore sealing process of the TiSiNiYN coating, the TiSiNiYN coating has a lower friction coefficient; compared with Example 1, Example 2 also has a significantly lower friction coefficient, indicating that the pore sealing process also has a reducing effect on the friction coefficient of the coating.

[0082] 4. Service life test

[0083] A cemented carbide end mill (purchased from Dongguan Chuanye Hardware Co., Ltd.) was used as the substrate to prepare the coating. The uncoated cemented carbide end mill was used as the control group to carry out the milling hardened steel experiment. The cutting line speed was 200m / s. The experimental material was hardened steel SKD11 with a hardness of 62HRC. The flank wear of 200μm was used as the life benchmark, and the cutting length was measured.

[0084] Table 3 Test results of cutting length

[0085]

[0086] The above test was performed on the TiSiNiYN coating prepared in Examples 1 to 7, and the results are shown in Table 3. As can be seen from Table 3, compared with Example 5, Example 6 and Example 7, the cutting length of Example 4 is significantly increased, indicating that the use of 2-nitrocinnamic acid in the detergent has an improved effect on the service life of the tool containing the TiSiNiYN coating; compared with Example 4, Example 7 and Example 5, and Example 3 and Example 2, the cutting length is also increased, indicating that after 2-amino-5-cyano-modified quartz is used in the sealing process of the TiSiNiYN coating and used in the preparation of the TiSiNiYN coating, the service life of the tool containing the TiSiNiYN coating is improved; compared with Example 1, the cutting length of Example 2 is significantly increased, indicating that the sealing treatment has an improved effect on the service life of the tool containing the TiSiNiYN coating.

[0087] 5. Binding strength test

[0088] The MFY-400 multifunctional material surface performance testing machine was used to test the bonding strength between the substrate and the coating.

[0089] Table 4 Test results of bonding strength

[0090]

[0091] The above test was performed on the TiSiNiYN coatings prepared in Examples 1 to 7, and the results are shown in Table 4. As can be seen from Table 4, compared with Example 5, Example 6 and Example 7, the bonding force is significantly increased, indicating that the use of 2-nitrocinnamic acid in the detergent has an enhancing effect on the bonding force between the TiSiNiYN coating and the substrate; compared with Example 4, Example 7 and Example 5, and Example 3 and Example 2, the bonding force does not change much, indicating that after 2-amino-5-cyano-modified quartz is used in the sealing process of the TiSiNiYN coating and used in the preparation of the TiSiNiYN coating, the bonding force between the TiSiNiYN coating and the substrate is not affected much; compared with Example 1, the bonding force of Example 2 does not change much, indicating that the sealing treatment has little effect on the bonding force of the coating.

[0092] The conventional techniques in the above embodiments are prior arts known to those skilled in the art, and thus will not be described in detail here.

[0093] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a TiSiNiYN coating for enhancing high temperature wear resistance, comprising: The substrate is cleaned with a detergent, and then arc ion plating is performed with a TiSiNiY alloy target in a nitrogen atmosphere to deposit a TiSiNiYN layer on the substrate to obtain a high-temperature wear-resistant coating; The detergent comprises: polyvinyl butyral, ethyl cellulose, and 2-nitrocinnamic acid, wherein the mass ratio of polyvinyl butyral to ethyl cellulose is 1:0.45-0.65, the concentration of 2-nitrocinnamic acid in the detergent is 6-8 g / L, and the dosage of the detergent is 0.1-0.15 mL / cm 2 ; The sealing agent is applied to the prepared TiSiNiYN coating by brushing, and after drying in the shade at room temperature, the temperature is raised to 102-110°C for 3-4.5 hours, and the heating rate is 0.8-1.5°C / min. After the insulation, the temperature is raised to 600-650°C at a heating rate of 1.8-3°C / min and sintered for 25-40 minutes to obtain a sealing layer; the thickness of the brushing treatment is 45-55 mg / cm 2 ; The sealing agent comprises sodium silicate nonahydrate, mica powder, modified quartz, silica sol, chromium trioxide and nickel oxide; The preparation of the sealing agent includes: adding silica sol to sodium silicate nonahydrate, stirring and mixing at 88-93° C. until it becomes clear, and after cooling to room temperature, adding mica powder, modified quartz, chromium trioxide and nickel oxide, and mixing evenly to obtain the sealing agent; The mass ratio of the above sodium silicate nonahydrate to silica sol is: 1:1.2-1.6; the mass ratio of sodium silicate nonahydrate to mica powder is: 1:0.4-0.6; the mass ratio of sodium silicate nonahydrate to modified quartz is: 1:0.5-0.8; the mass ratio of sodium silicate nonahydrate to chromium trioxide is: 1:0.3-0.42; the mass ratio of sodium silicate nonahydrate to nickel oxide is: 1:0.15-0.2; In the preparation of the modified quartz, the hydroxyl groups on the surface of the quartz are chemically bonded with 3-chloropropyltriethoxysilane, and then reacted with 2-amino-5-cyanopyridine to obtain the modified quartz; the mass ratio of quartz to 3-chloropropyltriethoxysilane is 1:0.15-0.3; the mass ratio of quartz to 2-amino-5-cyanopyridine is 1:0.3-0.

5.

2. The method for preparing a TiSiNiYN coating for enhancing high temperature wear resistance according to claim 1, characterized in that: The nitrogen pressure is controlled at 5-7 Pa.

3. The method for preparing a TiSiNiYN coating for enhancing high temperature wear resistance according to claim 1, characterized in that: The experimental parameters of the arc ion plating specifically include: target current of 100-200A, substrate bias of -100 to 100V, and deposition time of 1-6h.

4. The method for preparing a TiSiNiYN coating for enhancing high temperature wear resistance according to claim 1, characterized in that: In the TiSiNiY alloy target, by percentage, the content of Si is 8-15wt%, the content of Ni is 5-10wt%, the content of Y is 2-5wt%, and Ti is the balance.

5. The method for preparing a TiSiNiYN coating for enhancing high temperature wear resistance according to claim 1, characterized in that: The substrate cleaning method comprises: polishing the substrate, spraying a detergent on the surface of the substrate, peeling it off after drying to form a film, washing it with ultrapure water for 3-5 times, immersing the substrate in ultrapure water, wherein the mass volume ratio of the substrate to the ultrapure water is 1g:25-30mL, ultrasonic treatment for 25-35min, immersing the substrate in ethanol, wherein the mass volume ratio of the substrate to the ultrapure water is 1g:25-30mL, ultrasonic treatment for 25-35min, drying and setting aside.

6. The method for preparing a TiSiNiYN coating for enhancing high temperature wear resistance according to claim 1, characterized in that: The preparation method of the detergent comprises: adding polyvinyl butyral into a mixed solvent of ethanol and ethyl acetate, and after dissolving, adding ethyl cellulose and 2-nitrocinnamic acid, stirring and dissolving, and then setting aside.

7. The method for preparing a TiSiNiYN coating for enhancing high temperature wear resistance according to claim 6, characterized in that: The concentration of the 2-nitrocinnamic acid in the detergent is 6-8 g / L.

Citation Information

Patent Citations

  • TiSiNiN nano-composite coating and preparation method thereof

    CN106702338A

  • TiSiYN multi-component composite gradient tool coating and preparation method thereof

    CN109735803A